Feasibility and effectiveness of provider initiated HIV testing and counseling of TB suspects in Vizianagaram district, South India. - Shanta Achanta (Public Library of Science (PLoS), 2012)
Background Though internationally recommended, provider initiated HIV testing and counseling (PITC) of persons suspected of tuberculosis (TB) is not a policy in India; HIV seroprevalence among TB suspects has never been reported. The current policy of PITC for diagnosed TB cases may limit opportunities of early HIV diagnosis and treatment. We determined HIV seroprevalence among persons suspected of TB and assessed feasibility and effectiveness of PITC implementation at this earlier stage in the TB diagnostic pathway. Methods All adults examined for diagnostic sputum microscopy (TB suspects) in Vizianagaram district (population 2.5 million), in November-December 2010, were offered voluntary HIV counseling and testing (VCT) and assessed for TB diagnosis. Results Of 2918 eligible TB suspects, 2465(85%) consented to VCT. Among these, 246(10%) were HIV-positive. Of the 246, 84(34%) were newly diagnosed as HIV (HIV status not known previously). To detect a new case of HIV infection, the number needed to screen (NNS) was 26 among 'TB suspects', comparable to that among 'TB patients'. Among suspects aged 25-54 years, not diagnosed as TB, the NNS was 17. Conclusion The seroprevalence of HIV among 'TB suspects' was as high as that among 'TB patients'. Implementation of PITC among TB suspects was feasible and effective, detecting a large number of new HIV cases with minimal additional workload on staff of HIV testing centre. HIV testing of TB suspects aged 25-54 years demonstrated higher yield for a given effort, and should be considered by policy makers at least in settings with high HIV prevalence.